2018
DOI: 10.1002/anie.201812435
|View full text |Cite
|
Sign up to set email alerts
|

Active Edge‐Site‐Rich Carbon Nanocatalysts with Enhanced Electron Transfer for Efficient Electrochemical Hydrogen Peroxide Production

Abstract: A highly efficient, metal‐free carbon nanocatalyst is presented that possesses abundant active, oxygenated graphitic edge sites. The edge site‐rich nanocarbon catalyst exhibits about 28 times higher activity for H2O2 production than a basal plane‐rich carbon nanotube with a H2O2 selectivity over 90 %. The oxidative treatment further promotes the H2O2 generation activity to reach close to the thermodynamic limit. The optimized nanocarbon catalyst shows a very high H2O2 production activity, surpassing previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
193
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(197 citation statements)
references
References 36 publications
4
193
0
Order By: Relevance
“…The XRD pattern of NG-1000 exhibits a broad and negatively shifted peak (25.4°) from the (002) plane of graphite, indicating the exist of graphitic layers with relative small grain size and larger interplanar distance due to the presence of foreign atoms. [24] Compared with the amorphous nature of G-1000 and PG-1000, the enhanced degree of graphitization would be ascribed to the introduction of electron-rich nitrogen from urea, leading to an enhanced electroconductivity for further electrocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern of NG-1000 exhibits a broad and negatively shifted peak (25.4°) from the (002) plane of graphite, indicating the exist of graphitic layers with relative small grain size and larger interplanar distance due to the presence of foreign atoms. [24] Compared with the amorphous nature of G-1000 and PG-1000, the enhanced degree of graphitization would be ascribed to the introduction of electron-rich nitrogen from urea, leading to an enhanced electroconductivity for further electrocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Sa et al [31] also reported high activity for H 2 O 2 production on carbon nanomaterials with enriched oxygenated carbon edges. Zhou et al [32] studied activated carbon (AC) and revealed that the oxygen-containing groups on the AC function as oxygen reduction reaction sites for H 2 O 2 electrogeneration.…”
Section: Oxygen-doped Carbonaceous Materialsmentioning
confidence: 96%
“…This edge-enriched nanocarbon catalyst exhibits about 28 times higher activity for H 2 O 2 production than a basal plane-rich carbon nanotube (CNT) with a H 2 O 2 selectivity over 90%. [73] With the aid of Tafel slope and electrochemical impedance spectroscopic analysis, the authors pointed out that the first electron transfer ability from carbon to O 2 molecule (known as O 2 activation) is a prime determinant of the ORR activity. Chorkendorff et al screened seven commercially available carbon materials for 2e − ORR and revealed that H 2 O 2 selective materials have higher contribution from the C1s peak component correlated with aliphatic-type defects and edge carbon atoms, as opposed to intact graphitic carbon motifs.…”
Section: Defects and Heteroatoms Engineering On Carbon-based Catalystsmentioning
confidence: 99%
“…Reproduced with permission. [73] Copyright 2018, Wiley-VCH. b) Representative TEM image of mesoporous nitrogen-doped carbon (MNC).…”
Section: Defects and Heteroatoms Engineering On Carbon-based Catalystsmentioning
confidence: 99%